Effectiveness of Peer Teaching Learning Models in Lathe Machinery Practice Courses for Mechanical Engineering Education Program Students - Sarwi Asri; Hanif Hidayat; Muhammad Fariz Nasrullah (VANOS Journal of Mechanical Engineering Education, 2024)
The peer teaching learning model provides an opportunity for students to give each other knowledge to their peers. Peer teaching is a student-centred learning method. The purposes of this study are (1) to learn about the competence of students’ lathe practice after applying the learning model of peer teaching and (2) to know about the improvement of the competency of students’ lathe practice after applying the peer-teaching learning model. The method used in this research is quasi-experimental. The sample used in this research was 41 students of the Practical Class from the Mechanical Engineering Education Study Program. The data analysis used is normality test, homogeneity test, t-test, and N-Gain test. The results of the research show that (1) the competence of lathe practice of the students who apply a peer teaching learning model is in moderate categorized and (2) the application of a peer learning model is effective to improve the lathe practical competence of the students.